The cicadas (Hemiptera: Cicadidae) of Bolivia including the descriptions of fifteen new species, the resurrection of one genus and two species, seven new combinations, six new synonymies, and twenty-eight new records - Sanborn, Allen F. (Zootaxa, 2019)
The known cicada fauna of Bolivia is identified. Adusella Haupt, 1918 rev. stat. is resurrected and redescribed being elevated from junior synonym status with Odopoea Stål, 1861. Edholmbergi Delétang, 1919 rev. stat, n. syn. is elevated from junior synonymy of Odopoea and synonymized with Adusella rev. stat. Adusella insignifera (Berg, 1879) n. comb., Adusella signata Haupt, 1918 n. comb., and Adusella venturii (Distant, 1906c) n. comb. are transferred or returned to Adusella rev. stat. Carineta bilineosa Walker 1858b rev. stat., Carineta obtusa Walker 1858b rev. stat., Carineta tenuistriga Walker 1858c rev. stat. and Carineta diplographa Berg 1879 rev. stat. are removed from junior synonymy with Carineta fasciculata (Germar, 1821). Carineta obtusa rev. stat., n. syn., Carineta tenuistriga rev. stat., n. syn. and Carineta diplographa Berg 1879 rev. stat., n. syn. are considered junior synonyms of Carineta bilineosa rev. stat. Carineta limpida Torres 1948a n. syn. is shown to be a junior synonym of Carineta fasciculata. Carineta turbida Jacobi, 1907 is transferred to the genus Herrera Distant, 1905c to become Herrera turbida (Jacobi, 1907) n. comb. The genera Diceroprocta Stål, 1870, Orialella Metcalf, 1952, Quesada Distant, 1905c, and Nosola Stål, 1866a are assigned to the Guyalnina Boulard & Martinelli, 1996 within the Fidicinini Distant, 1905d. Tympanoterpes virgulata n. sp., Cracenpsaltria nana n. sp., Guyalna dasyeia n. sp., Guyalna fasciata n. sp., Guyalna polypaga n. sp., Parnisa santacruzensis n. sp., Carineta ensifera n. sp., Carineta hamata n. sp., Carineta pictilis n. sp., Carineta uncinata n. sp., Herrera concolor n. sp., Herrera freiae n. sp., Herrera melanomesocranon n. sp., Herrera phyllodes n. sp., and Herrera signifera n. sp. are described as new. The first records of Adusella insignifera (Berg, 1879) n. comb., Adusella venturii (Distant, 1906c) n. comb., Fidicina christinae Boulard & Martinelli, 1996, Fidicina ethelae (Goding, 1925), Fidicina robini Boulard & Martinelli 1996, Fidicinoides descampsi Boulard & Martinelli, 1996, Fidicinoides pauliensis Boulard & Martinelli, 1996, Fidicinoides sucinalae Boulard & Martinelli, 1996, Proarna alalonga Sanborn & Heath, 2014, Proarna bergi (Distant, 1892a), Proarna grisea (Fabricius, 1775), Proarna guttulosa (Walker, 1858b), Proarna insignis Distant, 1881a, Proarna strigicollis Jacobi, 1907, Guyalna distanti (Goding, 1925) Guyalna glauca (Goding, 1925), Guyalna platyrhina Sanborn & Heath, 2014, Guyalna viridifemur (Walker, 1850), Majeorona lutea Distant, 1906d, Carineta bilineosa Walker 1858b rev. stat., Carineta cearana Distant, 1906c, Carineta detoulgoueti Champanhet, 2001, Carineta doxiptera Walker, 1858a, Carineta maculosa Torres, 1948a, Carineta pilifera Walker, 1858c, Carineta rufescens (Fabricius, 1803), Carineta tetraspila Jacobi, 1907, and Herrera turbida (Jacobi, 1907) n. comb. are provided. The records for Adusella insignifera (Berg, 1879) n. comb. and Adusella venturii (Distant, 1906c) n. comb. are the first records of the tribe Zammarini Distant, 1905b, subtribe Zammarina Distant, 1905a, and genus Adusella, Tympanoterpes virgulata n. sp. is the first record of the genus Tympanoterpes Stål, 1861, Majeorona lutea Distant, 1906d is the first record for the genus Majeorona Distant, 1905d, Parnisa santacruzensis n. sp. is the first record of the genus Parnisa Stål, 1862a for Bolivia, specimens in the type series of Cracenpsaltria nana n. sp. represent the first record of the genus Cracenpsaltria Sanborn, 2016c in Ecuador, and the specimens of Herrera concolor n. sp., Herrera freiae n. sp., Herrera melanomesocranon n. sp., Herrera phyllodes n. sp., and Herrera signifera n. sp., and Herrera turbida (Jacobi, 1907) n. comb. and the new combinations to the genus are the first records of the genus Herrera Distant, 1905c for Bolivia, Brazil, French Guiana, and Peru. New records are provided to expand the ranges of Proarna alalonga Sanborn & Heath, 2014 and Carineta gemella to include Paraguay, the range of Dorisiana noriegai Sanborn & Heath, 2014 to include Paraguay and French Guiana, the range of Guyalna platyrhina to include Brazil, and the range of Carineta cearana to include Colombia. Previous records of Proarna bufo Distant, 1905d and Carineta fasciculata (Germar, 1821) are considered to be misidentifications P. bergi (Distant, 1892a) and Carineta bilineosa Walker 1858b rev. stat. so that P. bufo and C. fasciculata are removed from the cicada fauna of Bolivia as is Hemisciera maculipennis (de Laporte, 1832) which is shown to have been mistakenly attributed to Bolivia and Argentina. The non-Bolivian Carineta criqualicae Boulard 1986a, Carineta guianaensis Sanborn, 2011a, Carineta quinimaculata Sanborn, 2011a, and Carineta tigrina Boulard 1986a are reassigned to the genus Herrera to become Herrera criqualicae (Boulard, 1986a) n. comb., Herrera guianaensis (Sanborn, 2011a) n. comb., Herrera quinimaculata (Sanborn, 2011a) n. comb., and Herrera tigrina (Boulard, 1986a) n. comb., respectively. A discussion on the species status of Carineta fasciculata (Germar, 1821) is provided to clarify the taxon along with the new synonymy. The currently known Bolivian cicada fauna is comprised of 83 described species from 21 genera, seven tribes and three subfamilies with the new records and new species presented here increasing the known fauna by 107.5%.